If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + x = 5x + -7 Combine like terms: 5x + x = 6x 6x = 5x + -7 Reorder the terms: 6x = -7 + 5x Solving 6x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6x + -5x = -7 + 5x + -5x Combine like terms: 6x + -5x = 1x 1x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 1x = -7 + 0 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 5x-3=3x-9 | | -(7y+1)-(-6y-8)=6 | | 12x+5=89 | | x+(4.34-5x)=5 | | X=-24+2y | | 8h-(2h-5)=35 | | 8+5x-4x=7 | | 5x+3=4(-x+12) | | 9-5x+7x=27 | | H(t)=16t+32t+20 | | 7+5x=4x+8 | | -1.4x-2=-1.2x+7 | | 6x-5+2x=-5 | | -5x-10+6x=-4 | | 16(2x+3)-13(3x+4)= | | -4x+17=7 | | -13=3x+x+7 | | 112=6x+3x+4 | | x+y/3=5(x) | | -3/7y-14=7 | | k/3+(3k/5)=7 | | 10(z-1)-10(10z+2)= | | x+y/3=5 | | X^2+25=8 | | x^2+3x-18x=3 | | (y+1)(y-3)=4 | | 2/5-g=1/8 | | 13x+7x^2=5x^2-15x | | 54-x=281 | | 42/5-g=11/8 | | -968+423=86y-508-85y | | 32x^3-50x=0 |